Delayed cerebral ischemia after subarachnoid hemorrhage: from vascular spasm to cortical spreading depolarizations - Zheng, Zelong; Sánchez-Porras, Renán; Santos, Edgar; Unterberg, Andreas; Sakowitz, Oliver (Current neurovascular research, 2012)
Non-traumatic subarachnoid hemorrhage (SAH) represents about 5 to 6% of the overall incidence of stroke and - is associated with high morbidity and mortality...